Thermal Effect of Operatory Room Temperature, Surgical Drill Diameter, and Temperature of Irrigants at Different Depths of Implant Site Preparation - Thermographic Analysis on Goat Mandible - Priyanka Gangadhar Kapse; Kaustubh Suresh Thakare; Ramreddy Krishnarao Yeltiwar; Simran Rajkumar Parwani; Manish Arun Ashtankar; Nikita Bhagwandas Rathi (Wolters Kluwer Medknow Publications, 2022)
Background: Drilling of the implant site results in transient rise in temperature of the surrounding bone disrupting the bone healing process and implant stability. Overproduction of heat due to various factors at osteotomy site needs to be controlled as it hampers the final outcome of the procedure. Purpose: The purpose of this study was to evaluate various factors related to implant drills responsible for heat generation and temperature rise during osteotomy. Materials and Methods: A total of 64 bone specimens with dimensions of 15 mm × 15 mm were obtained from goat mandibles and were equally divided into Groups A and B with operating room temperature maintained at 25°C and 30°C, respectively. Osteotomies were performed using drills with diameters (4.2 mm and 5.6 mm) at various drilling depths (10 mm and 13 mm) with external saline irrigation temperatures (4°C and 25°C). Temperature change was recorded by laser thermometer. Results: The surgical drill depths, diameters, and room temperatures made no differences in temperatures at implant drilling sites whereas the temperatures of the irrigants provide sufficient heat control during drilling. Conclusion: Cooled saline provides beneficial effects in controlling the temperatures of osteotomy sites as compared to saline used at room temperature during implant site preparation.